Comparative study of EB-PVD gadolinium-zirconate and yttria-rich zirconia coatings performance against Fe-containing calcium-magnesium-aluminosilicate (CMAS) infiltration. (September 2021) - Chavez, Juan J. Gomez; Naraparaju, Ravisankar; Mikulla, Christoph; Mechnich, Peter; Kelm, Klemens; Ramana, C.V.; Schulz, Uwe
Highlights: Gadolinium zirconate (GZO) and yttria rich zirconia (65YZ) coatings were produced by EB-PVD. High-temperature CMAS infiltration resistance of EB-PVD GZO and 65YZ evaluated. The higher infiltration resistance of 65YZ demonstrated. The mechanisms, reaction kinetics and implications are discussed in detail. Abstract: This detailed study compare and contrasts the calcium-magnesium-aluminosilicate (CMAS) infiltration resistance behavior of electron-beam physical vapor deposition (EB-PVD) produced gadolinium zirconate (GZO) and yttria rich zirconia (65YZ, 65 wt % Y2 O3 rest zirconia) coatings. The infiltration kinetics, as well as the stability and protective nature of different reaction products, were studied by performing long term infiltration tests (up to 50 h) at 1250 °C. The results reveal that for the specific microstructures used in this study, 65YZ has a higher infiltration resistance and forms a thinner reaction layer compared to GZO. The analysis indicates that the better performance of 65YZ is associated with a synergetic reaction mechanism, which includes the formation of Ca-rich apatite and a uniform layer of a garnet phase. The formation of apatite requires more rare-earth (RE) in the case of GZO than its 65YZ counterpart, meaning that more Gd would be dissolved before forming apatite crystals, which leads to higher consumption of the GZO layer compared to that of 65YZ. The implications of these mechanisms are discussed in detail concerning the tendency of garnet formation, equilibration of the apatite phase with Ca and RE content, and the effects of the reduction in viscosity due to the RE dissolution into the glass. However, microstructural differences in the coatings used in this study might also affect the diverging infiltration resistance and reaction kinetics and need to be considered.